Application of surfactants for controlling destructive fungus contamination in mass cultivation of Haematococcus pluvialis. (December 2020) - Ding, Yi; Zhang, Aoqi; Wen, Xiaobin; Wang, Zhongjie; Wang, Kaixuan; Geng, Yahong; Li, Yeguang
Graphical abstract: Highlights: Surfactant SDBS can control P. sedebokerense contamination in H. pluvialis culture. Contamination can be inhibited by SDBS due to their different cell coverings. 7 mg L −1 SDBS prevented contamination in 5 m 2 and 20 m 2 open raceway ponds. No SDBS was detected in the H. pluvialis cells treated with 7 mg L −1 SDBS. SDBS can be effectively and economically applied in H. pluvialis mass culture. Abstract: Large-scale cultivation of Haematococcus pluvialis is frequently contaminated by the destructive fungus Paraphysoderma sedebokerense, which can cause huge losses in astaxanthin production. Here, we propose the use of four commercial surfactants to control P. sedebokerense contamination in H. pluvialis cultures. In laboratory experiments, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and primary alcohol ethoxylate treatments showed inhibitory effects on fungal contamination. Moreover, sodium dodecylbenzene sulfonate was the most promising because treatment at 7 mg L −1 was effective against fungal infection without negatively affecting the growth or astaxanthin contents of H. pluvialis . This could be ascribed to their different cell coverings and structures. Additionally, applying sodium dodecylbenzene sulfonate to open raceway ponds prevented fungal contamination, and astaxanthin production reached 1.82 g m −2 . Therefore, sodium dodecylbenzene sulfonate can be used as an effective and economical control agent for commercial production of astaxanthin from  H. pluvialis.